Placental stem cells-derived exosomes stimulate cutaneous wound regeneration via engrailed-1 inhibition - Zhang, Yan; Shi, Liyan; Li, Xiuying; Liu, Yang; Zhang, Guokun; Wang, Yimin (Frontiers in Bioengineering and Biotechnology, 2022)
Skin wounds generally heal by scarring, a fibrotic process mediated by the Engrailed-1 (EN1) fibroblast lineage. Scar is detrimental to tissue structure and function, but perfect healing in clinical settings remains to be explored. Recent studies have shown that mesenchymal stem cell (MSC) transplantation can reduce scarring. Here, we investigated the effects of placental MSCs (pMSCs) and exosomes derived from pMSCs (pMSC-exos) on wound healing using a full-thickness rat model. The results showed that pMSCs significantly accelerated the wound healing rate. Moreover, pMSCs improved the quality of wound healing, including regenerating cutaneous appendages (hair follicles and sebaceous glands), decreasing collagen I and increasing collagen III, and improving collagen pattern (basket-wave-like) in the healed skin. pMSC treatment also increased the regeneration of blood vessels. Importantly, all these listed effects of pMSCs were comparable to those of pMSC-exos, but significantly stronger than those of adipose MSC-derived exosomes (aMSC-exos). Further studies showed that the effects of pMSCs and pMSC-exos on wound regeneration may be mainly achieved via the down-regulation of the YAP signaling pathway, thus inhibiting the activation of EN1. In summary, pMSCs could effectively stimulate wound regeneration, and their effect could be achieved through their exosomes. This suggests that pMSC-exos treatment could be used as a novel cell-free approach to induce wound regeneration in clinical settings.